“EL” As Compounding in Extra Time Indonesia’s X Posts: A Morphological Study - Nauval Muhammad Darussalam; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2025)
This research investigates the usage of compounding in social media, specifically the utilization of “EL” as a morphological part of posts by Extra Time Indonesia on X (previously Twitter). This research aims to categorize the types and meanings of compounds formed with “EL” by analyzing data through the framework of morphological theory by Katamba and Plag. Qualitative descriptive methodology, which Creswell defines, is applied in this research to analyze language utilization within the social media setting. 10 data samples were analyzed based on the presence of “EL” as a compound part. The results indicate that 6 data are Exocentric compounds (60%), and 4 data are Endocentric compounds (40%), with no data of Copulative compounds identified (0%). Regarding the meanings, 4 data are Transparent meaning (40%), while 6 data are non-transparent meaning (60%), indicating that the interpretation does not always rely on contextual or cultural knowledge. Ultimately, this research demonstrates how social media users create meaning and identity through morphological creativity, especially on X. The term “EL” conveys the compound pattern in informal digital communication, providing insight into language adaptation within online communities and communication patterns. Keywords: Compounding, Social Media, Morphology